Percepción de los efectos económicos, financieros y sociales, por la aplicación de los incentivos tributarios: deducciones adicionales como mecanismos para incentivar la producción eco-eficiente; e inclusión laboral de trabajadores con discapacidad para el cálculo del impuesto a la renta en el sector económico, fabricación de productos de metal, excepto maquinaria y equipo en el periodo 2011 a 2013 del Distrito Metropolitano de Quito. - Bastidas Cumbal, Susana Elizabeth (2015)
This work focused on the study of the perception of economic, financial and social effects by implementing tax incentives: additional deductions as mechanisms to encourage eco-efficient production; and on the labor inclusion of disabled workers, for the calculation of income tax in the industry dedicated to the manufacture of metal products, except machinery and equipment within the Metropolitan District of Quito, through inquiry and interpretation of information provided by companies. We reviewed the basics, regulations linked to calculations, characteristics, determining the income tax and tax incentives in order to consolidate the knowledge and develop the theme of analysis through the study and research of the same. Tax incentives are regulated by the Internal Taxation Law, Organic Code of Production Trade and Investment (COPCI) and regulations there under; additionally Organic Disabilities Law was considered. We obtained information on the companies in the industry engaged in the manufacture of metal products, except machinery and equipment the Metropolitan District of Quito to structure the study of the topic according to the characteristics that these present, by using data collection techniques. Finally the implementation and tabulation of the results obtained through the survey, we conclude that for companies in the sector, there is the perception of getting financial and social economic results with the application of tax incentives.